Лісівничо-екологічні особливості динаміки деревного детриту в березняках Українського Полісся - Голяка, Марина Андріївна (НУБіП України, 2017)
Дисертація на здобуття наукового ступеня кандидата сільськогосподарських наук зі спеціальності 06.03.03 «Лісознавство і лісівництво». – Національний університет біоресурсів і природокористування України, Київ, 2017. Дисертаційну роботу присвячено вивченню лісівничо-екологічних особливостей динаміки деревного детриту в березняках Українського Полісся, в тому числі закономірностей формування відпаду дерев у молодняках берези повислої, терміну перебування сухостійних дерев у насадженні, швидкості деструкції деревного детриту берези повислої за умов Українського Полісся та встановленню видової приуроченості грибів до компонентів та класів деструкції деревного детриту. У дисертаційній роботі вперше встановлено морфологічні особливості динаміки деревного детриту в насадженнях берези повислої в Українському Поліссі, з’ясовано закономірності формування відпаду дерев у молодняках берези повислої, визначено середньозважений термін перебування сухостійних дерев у насадженнях берези повислої, встановлено взаємозв’язок динаміки деревного детриту та видового різноманіття мікобіоти, виявлено більшу кількість видів мікобіоти для деревної ламані у порівняні з мортмасою грубих гілок і сухостійними деревами, встановлено закономірність збільшення видового різноманіття мікобіоти деревного детриту від I до II–IV класів деструкції та зменшення кількості видів мікобіоти у разі досягнення V класу деструкції.
Thesis for awarding scientific degree of candidate of agricultural sciences in specialty 06.03.03 Silvics and silviculture. – National University of Life and Environmental Sciences of Ukraine, Kyiv, 2017. The dissertation is devoted to the study of forestry, and ecological features of accumulation and destruction mortmass in birch stands Ukrainian Polissya, including the regularity of the formation of tree mortality in young birch stands, time stay dead trees in the plantation, the velocity of degradation of birch deadwood in the conditions Ukrainian Polissya, and the establishment of specific confinement wood-destroying fungi to the components, and classes of mortmass destruction. The dissertation studied the dynamics of forest inventory parameters of dead trees in plantations of birch in the Ukrainian Polissya, the formation of dead trees in young stand of silver birch are researched, carried out the systematization of wood species composition of microbiota for the different components and destruction classes of birch mortmass, and performed their comparison. According to the forest inventory data, about 80 % of stands with a predominance of birch trees in Ukraine grow in the Ukrainian Polissya, which corresponds to 526 thousand hectares, or 17,3 % of the total area of forest areas covered by forest vegetation. The results of this research is established that actual area of birch plantations in Ukrainian Polesie can be more than 2 times than the data presented in official sources based on the results of forest management. Within 2 years from the moment of death of trees as a part of the stand, out of the total amount of dead wood, only third part of the birch trees is turned into logs. The main part of dead trees that turn into logs are thin thickness trees: d1,3=2–10 cm – 50 %, d1,3=11–20 cm – 32 %, d1,3>20 cm – 22 %. The average time stay dead trees of birch in stands is about 1 year old for young trees and 5 years for mature and overmature plantations. It has been established that the rate of destruction are thin thickness trees wood detritus (d≤ 10 cm) is k=0,236±0,016, and coarse wood detritus (d >10 cm) – k=0,125±0,018. It was found that some species of mycobiota occurred on certain components and destruction classes of birch coarse woody debris. Pattern similarity of mycobiota of the same and neighboring destruction classes of snags, logs, dead branches were found for silver birch forest of Ukrainian Polissya. Correlation analysis of the structure of fungal communities showed that powerful and strong groups are formed in the highest species diversity: logs of the III and V classes of degradation and snags of the III class decomposition. Four groups of homogeneous objects were identified by the similarity of the mycobiota at a Euclidean distance of less than 20. The first group includes the logs of the I class, the II class and the snags. The second group includes the IV class logs and the V grade of the destruction class. The third group includes logs III class and snags IV class logs of destruction. The fourth group includes dry class II and dry I class of destruction. At the same time, the objects that had the most excellent mycobiota composition from all other elements of wood detritus were identified, namely: the branches of the first class of destruction, and to a lesser extent the branches of the II–III class, have some similarity to the mycobiota with other components of the birch wood detritus. It was shown that the coarse woody debris components play an integral role in the formation of fungal complexes, strong determination and a clear correlation structure of which provide a basis for their use as biogeocenosis indicators for studying the effects of anthropogenic and other factors. Necessity to leave of logs and dead branch pieces of different destruction classes after forest using was established for maintaining of biodiversity in birch biogeocenoses.
Keywords: деревний детрит; Українське Полісся; береза повисла; клас деструкції; сухостій; деревна ламань; гілки; мікобіота; wood detritus; Ukrainian Polissya; birch; estruction classes; snags; logs; branches; mycobiota